In medias res: the diminishing of historical continuity in modern thought - Kara Te Water (Acta Academica, 2023)
Innovation and future predictions are discussed as the main goals of modern technology. Living in this empirical, modern world set on the future has the possibility of diminishing the value of historical continuity as observation and outcome-based theory take precedence over contemplation and tradition. It is proposed that the forgetfulness of modernity creates a stilted perception of time and thought which results in a dissonance between the perceiving subject and their surroundings. This is exacerbated by digital media as it mostly frames information as an attractive or trending source of amusement rather than as a possibility for edification. The result of this dissonance between the subject and their surroundings and the influence of digital media can be seen in the thoughtless or repetitive action and the abdication of action altogether in favour of escape from reality. This is problematised in as far constructive action for the well-being of the individual cannot be sustained in terms of the current engagement with digital technology.